Microstructural, dielectric and ferroelectric properties of Sr0.8Bi2.15Ta2O9 ceramics synthesized by microwave processing technique. (2nd January 2020) - Sahu, R.; Kumar, P.
ABSTRACT: Sr0.8 Bi2.15 Ta2 O9 (SBT) ceramics were synthesized by microwave-assisted solid-state reaction route. SBT ceramics were sintered at three different temperatures namely 1050°C, 1100°C and 1150°C for 30 min, respectively. XRD study confirmed the retention of single phase of SBT ceramics sintered at 1050°C and 1100°C. Plates like with non-uniform distribution of grains were observed from the FESEM study. Dielectric constant and dielectric loss were found to decrease with the increase of sintering temperature. From room temperature P–E loop study, remnant polarization and coercive field were found to increase with the increase in sintering temperature. From the J–E plot study, leakage current was found to decrease with the increase in sintering temperature. Minimal degradation of polarization was obtained from fatigue characteristics. SBT ceramics sintered at 1100°C show better ferroelectric properties and make it suitable for memory applications.